Manajemen Pelayanan Keamanan Masyarakat Berbasis IT Guna Menjaga Stabilitas Keamanan Dan Ketertiban Masyarakat (Program Panic Button on hand POLRES Malang Kota) - Decky Hendarsono* (Universitas Airlangga, 2017)
The increasing number of crimes forces the need for security to be the main thing and is an important requirement for humans to run daily activities. This study aims to analyze and describe efforts to optimize community service programs in the field of IT-based community service in Malang City Police. The research method used is qualitative, with interview data collection techniques and observation. The results of the study were discussed using two concepts, namely the first question regarding management of IT-based community services in Malang City Police, where those measured using the concept of POAC (planning, organizing, controling, actuating). Meanwhile, the second question discussed about efforts to optimize the management of public security services in the field of IT-based community security uses the 4m concept (man, money, material and method).